Peruvian prehistory : an overview of pre-Inca and Inca society - Keatinge, Richard W. Ed (Cambridge University Press, 1992)
Peruvian Prehistory offers an authoritative survey of the cultural evolution of Peru from the appearance of the first inhabitants around 10,000 BC to the arrival of the Spanish in 1534. The book is divided chronologically into three main parts, which examine in turn the highland and lowland zones in the Preceramic and Initial periods; the development of complex society at Chavin, Tiwanaku and Fluari and in the Moche and Nazca cultures; and the culmination of this process, the Pan-Andean empire of the Incas, and the way this can be studied through a combination of archaeology and ethnohistoric research. A fourth, concluding section deals with the often neglected tropical forest region of Peru and its formative influence on the evolution of Andean culture. The first collective assessment of Peruvian archaeology for a generation, this volume traces the processes of political, social and economic change in Andean civilisation in a manner that will attract many with no specialist interest in Peru.